2013
DOI: 10.5114/aoms.2013.36987
|View full text |Cite
|
Sign up to set email alerts
|

State of the art paper Function and expression of prolyl hydroxylase 3 in cancers

Abstract: Hypoxia inducible factor (HIF) is a product of tumor cells that plays an important role in protecting tumor cells and adjusting to low oxygen tension through driving the progression and aggressiveness of tumors and changing the growth, angiogenesis, differentiation and metastasis of tumors. Prolyl hydroxylase 3 (PHD3) is a member of PHDs that are induced in hypoxia. Many studies have shown that PHD3 not only can hydroxylate HIF-1α, but also has various other biological functions. Thus PHD3 plays significant ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Correlation analysis of PHD3 expression with regards to the clinicopathological features of gastric cancer revealed that increased PHD3 expression was correlated with a high degree of differentiation of cancer cells, early TNM stage and decreased lymph node metastasis. These results are consistent with previous studies (20,27) and suggest that PHD3, or a putative protein target downstream of PHD3, may participate in tumor progression. Su et al (25) reported that PHD3 was upregulated in well-differentiated specimens of pancreatic cancer, whereas undifferentiated tumors exhibited reduced PHD3 expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Correlation analysis of PHD3 expression with regards to the clinicopathological features of gastric cancer revealed that increased PHD3 expression was correlated with a high degree of differentiation of cancer cells, early TNM stage and decreased lymph node metastasis. These results are consistent with previous studies (20,27) and suggest that PHD3, or a putative protein target downstream of PHD3, may participate in tumor progression. Su et al (25) reported that PHD3 was upregulated in well-differentiated specimens of pancreatic cancer, whereas undifferentiated tumors exhibited reduced PHD3 expression.…”
Section: Discussionsupporting
confidence: 93%
“…Chen et al (19) demonstrated that PHD3 protected the intestinal epithelial barrier from ulcerative injury, which is one of the causes leading to the development of gastric cancer. However, although the actions of PHD3 in the suppression of angiogenesis, growth and differentiation of tumor cells have previously been reported (20), the detailed molecular mechanisms implicating PHD3 in gastric cancer have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The present study aimed to explore the association between PHD3 and HIF2α expression in HCC (under hypoxic conditions). Several studies have demonstrated that PHD3 serves a novel role in the progression and prognosis of cancer (15-24); PHD3 is also able to induce apoptosis and inhibit proliferation in cancer cells (22)(23)(24)(25)(26)(27)(28)(29). To the best of our knowledge, the present study is the first to report that PHD3 overexpression induces apoptosis and inhibits growth and proliferation in HCC cells.…”
Section: Introductionmentioning
confidence: 59%
“…Thus, PHD3 appears to have oncosuppressive properties in many different tumors, with low levels of the enzyme correlating with poor outcome. This is the case of pancreatic, colorectal, and breast cancers [ 53 ], plasma cell neoplasia [ 54 ], pheochromocytoma [ 55 ] and glioblastoma [ 56 ], where PHD3 regulates neuronal apoptosis. PDH3, together with its downstream effectors, defines a pathway that is responsible for the elimination of excess neuroblasts during normal embryological development when growth factors, such as NGF, become limiting.…”
Section: Discussionmentioning
confidence: 99%